Preoperative transfusion versus no transfusion policy in sickle cell disease patients: a randomized trial. (5th March 2020) - Elshinawy, Mohamed; Al Marhoobi, Nada; Al Abri, Rashid; Nazir, Hanan F.; Khater, Doaa; Maktoom, Manar; Al‐Rawas, Abdulhakim; Mevada, Surekha T.; Elghamry, Islam; Wali, Yasser
ABSTRACT: BACKGROUND: Many children with sickle cell disease (SCD) indicated for adenotonsillectomy receive pre‐operative transfusion therapy, either simple or exchange transfusion, in order to reduce surgical and sickle cell disease‐related complications. SUBJECTS AND METHODS: This is a prospective randomized controlled clinical trial aiming to compare between preoperative simple transfusion and no transfusion in pediatric patients with sickle SCD admitted in Sultan Qaboos University Hospital, Muscat, Oman for adenotonsillectomy during the period from January 2014 through June 2018. They were randomly assigned into two arms (simple transfusion and no transfusion). RESULTS: Postoperative SCD‐related complications have been encountered in 6 out of 138 patients (4.3%). There was no statistically significant difference between the two studied groups as regards the development of surgical or SCD‐related complications (p = 0.6 and 0.8 respectively). The length of postoperative hospital stay was comparable in the two groups. (p = 0.607). SCD‐related complications occurred exclusively in cases with homozygous sickle anemia (4 out of 81 = 4.9%). CONCLUSION: Sickle cell disease patients with a hemoglobin level above 7.5 g/dL do not need PRBCs transfusion prior to adenotonsillectomy. This approach did not increase the risk of postoperative surgical or SCD‐related complications.